2016
DOI: 10.1038/srep37809
|View full text |Cite
|
Sign up to set email alerts
|

Associations of blood lead levels with reproductive hormone levels in men and postmenopausal women: Results from the SPECT-China Study

Abstract: We examined whether blood lead levels (BLLs) were associated with reproductive hormone levels in a cross-sectional study using data from the SPECT-China study. We selected 2286 men and 1571 postmenopausal women without hormone replacement therapy. BLLs, blood cadmium, total testosterone (TT), oestradiol (E2), luteinizing hormone (LH), follicle stimulating hormone (FSH) and sex hormone binding globulin(SHBG) levels were measured. The results showed that median values (interquartile range) of BLLs were 44.00 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
(58 reference statements)
2
10
1
Order By: Relevance
“…A few epidemiological studies have explored the association between heavy metal and FSH levels. Our results are consistent with those of earlier works from the USA and China [1619]. In China, a recent study found statistically significant positive associations between the blood lead level and FSH concentration in postmenopausal women, but the significance was marginal in men [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A few epidemiological studies have explored the association between heavy metal and FSH levels. Our results are consistent with those of earlier works from the USA and China [1619]. In China, a recent study found statistically significant positive associations between the blood lead level and FSH concentration in postmenopausal women, but the significance was marginal in men [19].…”
Section: Discussionsupporting
confidence: 93%
“…Also, other US data showed a positive association between lead and testosterone levels in males, and cadmium and FSH levels in perimenopausal women [1718]. In China, a recent study found positive associations between lead and testosterone levels in men and between lead and FSH and LH levels in postmenopausal women [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above toxic effects, environmental and occupational exposure to lead may cause of male infertility by reducing sperm count motility, viability, normal forms and detectable levels[ 24 ]. Lead exposure was also associated with reproductive hormone levels in Chinese males and postmenopausal females[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-essential metal elements, such as cadmium, lead, and mercury, have endocrine-disrupting properties even at low concentrations. A positive relationship between environmental cadmium exposure and testosterone levels has also been shown among adult males and females [1520], and several epidemiologic studies have indicated that environmental lead exposure is associated with increased testosterone levels in U.S., Croatian, and Chinese men [2123]. The research regarding environmental mercury exposure and testosterone levels in humans is limited.…”
Section: Introductionmentioning
confidence: 99%